2013
DOI: 10.1542/peds.2013-0912
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopy With N-Acetylcysteine Lavage in Severe Respiratory Failure From Pertussis Infection

Abstract: Pertussis is an illness that causes significant morbidity and mortality, especially in infants younger than 3 months old. In the most severe cases, it can cause pneumonia, respiratory failure, acute respiratory distress syndrome, pulmonary hypertension, and death. There are reports of using rescue extracorporeal membrane oxygenation (ECMO) as a rescue therapy. However, the mortality of ECMO with pertussis is higher than with other causes of pediatric respiratory failure. We report here the case of a 2-month-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Despite inhaled NAC has been used safely for decades as a mucus-dissolving treatment in respiratory diseases associated to abundant and/or thick mucus production (e.g., CF, COPD, bronchiectasis), the actual NAC concentrations achievable in the ELF after topical administration have never been determined. Nonetheless, considering the multiple-dosage regimes of nebulized administration (e.g., 1–10 mL of 200 mg/mL solution every 6–8 h), the higher performance of last-generation nebulizers, and the possibility of direct instillation, topical NAC could reach the ELF concentrations needed for exerting the antimicrobial and antibiofilm potentiation of colistin activity [16,29]. In addition, NAC dry powder formulations have recently been implemented, with the aim of potentiating the penetration through the respiratory mucus of inhaled antibiotics (i.e., clarithromycin and fluoroquinolones) [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Despite inhaled NAC has been used safely for decades as a mucus-dissolving treatment in respiratory diseases associated to abundant and/or thick mucus production (e.g., CF, COPD, bronchiectasis), the actual NAC concentrations achievable in the ELF after topical administration have never been determined. Nonetheless, considering the multiple-dosage regimes of nebulized administration (e.g., 1–10 mL of 200 mg/mL solution every 6–8 h), the higher performance of last-generation nebulizers, and the possibility of direct instillation, topical NAC could reach the ELF concentrations needed for exerting the antimicrobial and antibiofilm potentiation of colistin activity [16,29]. In addition, NAC dry powder formulations have recently been implemented, with the aim of potentiating the penetration through the respiratory mucus of inhaled antibiotics (i.e., clarithromycin and fluoroquinolones) [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations at which the antimicrobial and antibiofilm activities of NAC have been observed were variable but usually higher than those achievable by systemic routes of administration (i.e., oral, intramuscular or intravenous), which can result in peak plasma concentrations of 0.2–1.2 mg/ml [ 8 ]. However, NAC can also be administered topically, either by nebulization or direct instillation [ 2 , 9 ], and reach at the site of infection the higher concentrations needed for the antimicrobial and antibiofilm activity. Despite initial concerns about the potential negative interaction of NAC on antibiotic activity [ 10 ], two recent articles have demonstrated that NAC does not negatively affect the activity of the major antibiotic classes, with the exception of carbapenems [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our patient had developed a severe pertussis infection that is associated with intraluminal bronchiole obstruction likely secondary to mucus (9, 10). Lung recruitment may have been limited by the inability to suction and clear mucus secretions, and therefore initially bronchoscopy was successfully recruited his lungs.…”
Section: Discussionmentioning
confidence: 94%